Implementación de un sistema de información para las capacitaciones en línea en Compudemano (2011)
Compudemano is an organization focused on selling Apple computers, and other brands and offer services such as training, technical support, and sale of other brands, this company is interested in having an information system enabling it to offer courses online on the products that they sell, the project will solve this need by implementing an information system.